2018
DOI: 10.1111/head.13286
|View full text |Cite
|
Sign up to set email alerts
|

Migraine Care Challenges and Strategies in US Uninsured and Underinsured Adults: A Narrative Review, Part 1

Abstract: There are many barriers and challenges that affect people with migraine who are underinsured or uninsured, particularly those of under-represented racial backgrounds and of lower socioeconomic status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…7 In both incidence and severity, people occupying marginalized social locations (SL) bear the greatest migraine burden. 1214 SL is a dynamic position on the social hierarchy determined by the ways intersecting socially ascribed identities are valued within shifting social, political, and economic contexts: racialized populations, people with less education, living in poverty, un- or underemployed, and those with high levels of chronic stress due to the unequal distribution of health-damaging experiences, for example, lack of clean and reliable food sources, unstable housing, prejudice and discrimination, and exposure to violence. 15,16…”
Section: Migraine: Incidence Burden and Caim Usementioning
confidence: 99%
“…7 In both incidence and severity, people occupying marginalized social locations (SL) bear the greatest migraine burden. 1214 SL is a dynamic position on the social hierarchy determined by the ways intersecting socially ascribed identities are valued within shifting social, political, and economic contexts: racialized populations, people with less education, living in poverty, un- or underemployed, and those with high levels of chronic stress due to the unequal distribution of health-damaging experiences, for example, lack of clean and reliable food sources, unstable housing, prejudice and discrimination, and exposure to violence. 15,16…”
Section: Migraine: Incidence Burden and Caim Usementioning
confidence: 99%
“…2,7 Plausible solutions and strategies to migraine care in underinsured and uninsured adults have been described. 45,46 This analysis showed that race had a significant effect on the rate of consultation. Current consultation rates were highest among Blacks and/or African Americans and lowest among those reporting race categorized as "other."…”
Section: Ta B L E 4 Effect Of Sociodemographic Characteristics On Traversing Barriers To Carementioning
confidence: 89%
“…This is a concern, especially because the prevalence of migraine is greater among individuals in lower versus higher income groups 2,7 . Plausible solutions and strategies to migraine care in underinsured and uninsured adults have been described 45,46 …”
Section: Discussionmentioning
confidence: 99%
“…The need for equitable Medicaid coverage raises the more general concern about pervasive disparities in the care for headache disorders. Racial and socioeconomic barriers limit access to headache specialty care 86,87 . Low income is associated with higher migraine attack frequency, 88 and some under‐represented groups have a higher prevalence of both poverty and migraine overall (eg, Native Americans) 87 .…”
Section: Future Directionsmentioning
confidence: 99%